2023
DOI: 10.1097/dss.0000000000003688
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Fractional CO2 Laser on Cleft Lip Scars: A Single-Blind Randomized Controlled Cohort Study

Abstract: BACKGROUND Scar is one of the most common complications for patients with cleft lip. Fractional CO2 laser is an effective method to improve the appearance of scars. However, there are no published articles about the optimal time for applying. OBJECTIVE To determine the optimal time to apply a fractional CO 2 laser for the treatment of postsecondary repair scars in patients with cleft lip. METHODS Forty-two patients with linear scarring after cleft lip repair were recruited from November 2021 to October 2022. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…34 The optimal timing of laser treatment is another area of investigation, and whether it is better to intervene early or wait for scar maturation. Chi et al 35 conducted a 2023 study treating 42 patients with a linear cleft lip scar in a singleblind, randomized controlled trial to compare fractionated CO 2 to no intervention. Thirty of these patients in the treatment arm underwent laser treatment at either 1, 3, 6, or 12 months.…”
Section: Ablative Laser Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The optimal timing of laser treatment is another area of investigation, and whether it is better to intervene early or wait for scar maturation. Chi et al 35 conducted a 2023 study treating 42 patients with a linear cleft lip scar in a singleblind, randomized controlled trial to compare fractionated CO 2 to no intervention. Thirty of these patients in the treatment arm underwent laser treatment at either 1, 3, 6, or 12 months.…”
Section: Ablative Laser Outcomesmentioning
confidence: 99%
“…Using the VSS, the study found that the laser treatment arm had significantly improved scar appearance, and that those in the 1-month postoperative laser treatment group had better outcomes, suggesting that early laser intervention may portend better scar appearance. 35 While the results of these studies are promising and show that laser does play a role in adjuvant scar treatment, some studies have failed to demonstrate efficacy. A 2023 split-scar prospective study by Lin et al 36 performed fractional CO 2 laser treatment on 30 incisions after skin cancer resection on the limbs.…”
Section: Ablative Laser Outcomesmentioning
confidence: 99%
“…In terms of treatment timing, some scholars advocate early laser intervention for scar, such as 1-4 weeks after surgery (32,33) because it can promote the reduction of scar hyperplasia index, and the duration of scar hyperplasia is also signi cantly shortened, with no obvious postoperative adverse reactions (34). A study published in 2023 showed that early treatment with CO 2 laser was more effective than later treatment within a month after surgery (11). However, it is also believed that scar at maturity (3 months to 1 year after scar formation) is more convenient to treat, so scar boundaries are clearer and its properties are more stable, and it is di cult to transform into other tissues (35).…”
Section: Strengths and Limitations Of The Reviewmentioning
confidence: 99%
“…Timely and accurate surgical treatment including plastic surgery and oralmaxillofacial surgery(8) as well as special postoperative care is of great signi cance for children with cleft lip and/or palate (9). Regrettably, the mechanical tension caused by a child's inevitable facial muscle movements (such as crying and sucking) has an adverse effect on postoperative wound healing, which can lead to enlarged scars and long-term development that can affect the patients' physical and mental health (10,11). So far, great progress has been made in the treatment of scar after cleft lip surgery.…”
mentioning
confidence: 99%
“…Ultimately, 18 eligible articles were obtained. Thirteen RCTs focused on the effects of the interventions to prevent surgical scars and reported VSS measurements(3,5,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The other 7 RCTs were conducted on effects of the interventions to prevent surgical scars and depicted the OSAS measurements(3,17,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%